Migrasjon og mobilitet - handlinger, mønstre og forståelser i norsk sammenheng - Villa, Mariann (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Migration and mobility transform the daily lives and surroundings of those who travel and relocate, as well as the places they move from and to. This anthology presents some of the disparate perspectives, theories and methodologies that characterize research on migration and mobility. Through the book's eleven chapters the authors shed light on international research on migration and Norwegian research on transience and tourism. The contributions include empirical studies of immigrant workers and their welfare, marginalization in the job market and opportunities for successors, social mobility in the new country, repro-migration, and local community responses and adaptation to mobility. The book also provides a comprehensive discussion of Norwegian integration policy and methodological challenges and blind spots in Norwegian migration research. On the whole, Migration and Mobility - Actions, Patterns and Perceptions in the Context of Norway is a significant contribution to the advancement of research in these areas. The book will be of interest to everyone concerned with the study of migration and mobility in Norway, but especially to researchers in the field and students of sociology, social anthropology, human geography and other social sciences at the higher educational level. Migration and Mobility has been edited by Mariann Villa (professor of sociology, NTNU), Erik T. Valestrand (doctoral fellow in sociology, NTNU) and Johan Fredrik Rye (professor of sociology, NTNU).